Feature. (November 2018) - Ismail, Rita; Voss, Joachim G.; Woods, Nancy Fugate; John‐Stewart, Grace; Lowe, Celia; Nurachmah, Elly; Yona, Sri; Muhaimin, Toha; Boutain, Doris
Abstract : N/A: Few international studies document the concerns of women living with HIV (WLWH) who were infected by their intravenous drug‐using husbands. Our content analysis described the concerns of this population by analyzing 12 interviews with WLWH. Three main concerns were discussed by the women: dealing with anger and being a dedicated wife, going home to one's parents as the only place to go, and being strong and staying alive for the children. Dealing with their own emotional responses to the HIV diagnosis, lacking financial resources after the husband's death, and remaining focused on staying healthy were major issues in their stories. Indonesia needs large‐scale public HIV education campaigns about the risks women encounter as wives to husbands who use intravenous drugs as well as campaigns to educate husbands about their risks. Nurses need to encourage women to get tested during prenatal care to prevent infecting their children.